PENYELESAIAN SENGKETA TANAH SESUDAH BERLAKUNYA UNDANG-UNDANG POKOK AGRARIA - Istijab Istijab (Universitas Widya Gama Malang, 2018)
Since September 24th, 1960, land disputes have floated in respect to the government’s policies which are inconsistent, overlapping and ambivalent. The UUPA No. 5/1960 has been emasculated by the released of sector regulations such as mining regulation, forestry regulation, local government regulation (Autonomy) that each of them has put the land on the same object, whilst each department has different viewed in understanding the object. The different understanding of land as the object has opened to conflict of interest that substantially causes UUPA No. 5/1960 to compartmentalization. Finally, how to identify the land dispute cases, the causal factor of land dispute and solution of the cases based on the source, principle and prevailed regulation must be discussed. Kata Kunci : UUPA, sengketa tanah dan kebijakan pemerintah